WHITE TURMERIC (Curcuma zedoaria): ITS CHEMICAL SUBTANCE AND THE PHARMACOLOGICAL BENEFITS - Putri, Muflikha Sofiana (Majority, 2014)
Abstract Cancer is a disease caused by the growth of body tissue cells that are not normal. Treatment of cancer other than using chemical drugs, also can use phytotherapeutic agent, that is a standard herbal consist of active subtances derived from plant parts. Some studies suggest that white turmeric (Curcuma zedoaria) is one of the herbs that can be processed into herbal medicine. The chemical subtances on white turmeric contains a lot of benefits such as anticancer, antifungal, antiamebic, larvicides, antimicrobial, antioxidant, antiplasmodial, hypo-allergenic, and analgesics. Based on these data, it can be concluded that white turmeric contains chemical subtances like curcuminoid, RIP (Ribosome Inacting Protein), isocurcumenol, demothxycurcumin, bisdemothxycurcumin, epicurzerenone, curdione, and ethyl p-methoxycinnamate which serves to disable the development of cancer cells and inhibits the growth of cancer cells. In addition, white turmeric also contains chemical subtances such as curzerenone, zedoaron, essential oils, diferuloylmethan, flavonoids, curcumin, trimethoxyflavone, tetramethoxyflavone, tetrahydrodemethoxycurcumin, dihydrocurcumin, and polyphenols as pharmacological benefits. Keywords: anticancer, antimicrobial, Curcuma zedoaria, white turmeric Abstrak Kanker adalah suatu penyakit yang disebabkan oleh pertumbuhan sel-sel jaringan tubuh yang tidak normal. Pengobatan kanker selain menggunakan obat kimia, juga dapat menggunakan agen phytotherapeutic, yaitu obat herbal standar yang terdiri dari bahan aktif yang berasal dari bagian tanaman. Beberapa penelitian mengatakan bahwa kunyit putih (Curcuma zedoaria) merupakan salah satu tumbuhan berkhasiat yang dapat diolah menjadi obat herbal. Kandungan senyawa kimia pada kunyit putih mengandung banyak manfaat seperti antikanker, antifungal, antiamebic, larvasida, antimikroba, antioksidan, antiplasmodial, antialergi, dan analgetik. Berdasarkan data tersebut, dapat ditarik kesimpulan bahwa kunyit putih mengandung senyawa kimia kurkuminoid, RIP (Ribosome Inacting Protein), isocurcumenol, demothxycurcumin, bisdemothxycurcumin, epicurzerenone, curdione, dan ethyl p-methoxycinnamate yang berfungsi menonaktifkan perkembangan sel kanker dan menghambat pertumbuhan sel kanker. Selain itu, kunyit putih juga mengandung senyawa kimia seperti curzerenone, zedoaron, minyak atsiri, diferuloylmethan, flavonoid, kurkumin, trimethoxyflavone, tetramethoxyflavone, tetrahydrodemethoxycurcumin, dihydrocurcumin, dan polifenol yang bermanfaat secara farmakologis. Kata kunci: antikanker, antimikroba, Curcuma zedoaria, kunyit putih